2021
DOI: 10.3389/fped.2021.676616
|View full text |Cite
|
Sign up to set email alerts
|

The Genotype and Phenotype of Proline-Rich Transmembrane Protein 2 Associated Disorders in Chinese Children

Abstract: Objectives: To study the genetic and clinical characteristics of Chinese children with pathogenic proline-rich transmembrane protein 2 (PRRT2) gene-associated disorders.Methods: Targeted next generation sequencing (NGS) was used to identify pathogenic PRRT2 variations in Chinese children with epilepsy and/or kinesigenic dyskinesia. Patients with confirmed PRRT2-associated disorders were monitored and their clinical data were analyzed.Results: Forty-four patients with pathogenic PRRT2 variants were recruited. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…To date, there are 2 different models for PRRT2 topology in the literature; one model predicts that the long N-terminal portion is an intracellular domain, 19 , 20 whereas the other model predicts the N-terminal portion as an extracellular domain. 21 , 22 A recent study further characterized the PRRT2 protein topology using TMHMM (TransMembrane prediction using Hidden Markov Models), a transmembrane helix prediction program, 23 which supports the model of extracellular localization of the N-terminal region. Therefore, in this report, we adapted the gene/protein structure and the membrane topology of PRRT2 with a long N-terminal extracellular domain, 2 transmembrane domains (M1 and M2) separated by an intracellular (cytoplasmic) domain, and a short C-terminal extracellular domain ( Figure 5, A and B ).…”
Section: Resultsmentioning
confidence: 91%
“…To date, there are 2 different models for PRRT2 topology in the literature; one model predicts that the long N-terminal portion is an intracellular domain, 19 , 20 whereas the other model predicts the N-terminal portion as an extracellular domain. 21 , 22 A recent study further characterized the PRRT2 protein topology using TMHMM (TransMembrane prediction using Hidden Markov Models), a transmembrane helix prediction program, 23 which supports the model of extracellular localization of the N-terminal region. Therefore, in this report, we adapted the gene/protein structure and the membrane topology of PRRT2 with a long N-terminal extracellular domain, 2 transmembrane domains (M1 and M2) separated by an intracellular (cytoplasmic) domain, and a short C-terminal extracellular domain ( Figure 5, A and B ).…”
Section: Resultsmentioning
confidence: 91%
“…Case 1 carried an unreported variant, c.397delG (p.E133Nfs*43), which was predicted to be deleterious and pathogenic by multiple software programs. Luo et al ( 3 ) reported that seven family members carrying heterozygous mutations in the PRRT2 gene had no clinical symptoms associated with PRRT2 -related disorders, suggesting incomplete penetrance of the PRRT2 mutations. In the current study, the variant in case 5 was inherited from the father who showed no clinical phenotype, also suggesting incomplete penetrance.…”
Section: Discussionmentioning
confidence: 99%
“…In humans and rodents, PRRT2 is a neuroprotein that is most abundantly expressed in the cerebellum, basal ganglia, and neocortex. Mutations in PRRT2 are associated with a variety of neurological disorders, such as BFIE, paroxysmal kinesigenic dyskinesia, and infantile convulsions and choreoathetosis, which account for more than 90% of all cases ( 3 , 23 ). Other rare phenotypes, including seizures, ictal ataxia, and hemiplegic migraine, have also been reported, suggesting significant phenotypic heterogeneity resulting from PRRT2 mutations ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations